Fatal Subarachnoid Hemorrhage due to Intravascular Adrenaline Absorption - Bansal, Sonia; Rao, Ganne S. Umamaheswara; Syeda, Seham; Surve, Rohini M. (Journal of Neuroanaesthesiology and Critical Care, 2020)
Vasoconstrictors are commonly administered with local anesthetics (LAs) to decrease intraoperative bleeding. However, inadvertent systemic absorption of adrenaline is not uncommon and is associated with significant hemodynamic consequences and arrhythmias, which are usually inconsequential. We report a case of suspected intravascular adrenaline absorption in a 1-year-old girl with craniosynostosis, which led to subarachnoid hemorrhage, herniation, and death.
Keywords: adrenaline; intravascular; subarachnoid hemorrhage; pulmonary edema